Paul Oderborn’s Unknown Poem about Lithuania - Narbutas, Sigitas (Senoji Lietuvos literatūra, 2018)
In 2017, a little-known work by Paul Oderborn, a Lutheran pastor from Kaunas, was found at the Saxon State and University Library. Hymnus de antiqua et illustri Heleboviciorum gente (A Hymn about the Ancient and Glorious Family of Glebavičius) was published at Jan Karcan’s printing house in Vilnius in 1583. It dwells on the history of Lithuania placing more emphasis on Gediminas and the founding of Vilnius, describes the Glebavičius (Hlebowicz) family, and mentions prominent members of this family. Hymnus is written as a frame narrative: lines 1–4 describe the content of Hymnus and appeal to Muses for inspiration and assistance, and the further plot (lines 5–606) is framed within the narrator’s encounter with Neptune and the Muses at the Nemunas River. In lines 5–20, Neptune emerges from the Nemunas and shows the narrator Jonas Glebavičius’s (Jan Hlebowicz) coat-of-arms consisting of four fields; in lines 21–466, Kleio, the muse of history, tells about the Leliwa in the top left field of the coat of arms and about Glebavičius’s family on his father’s side. In lines 467–535, Kleio glorifies the Lion in the top right field of the coat of arms, maternal ancestor Jaunutis Gediminaitis, Prince of Zaslavl, and his progeny. In lines 536–582, the Muse sings about Dombrowa at the bottom left field and other nobles of the Glebavičius’s family – the Kiška family and Stanislovas Kiška (Stanisław Kiszka) among them. In lines 583–606, Kleio glorifies Vytis (The coat of arms of Lithuania, consisting of an armour-clad knight on horseback holding a sword and shield), the Algirdaičiai (Algirdids) and their descendant Ona Zaslavskytė (Sluckaitė; Anna Zaslawska), Glebavičius’s mother. Lines 607–610 are the closing lines of the poem: Kleio stops talking, Apollo begins playing the kithara, the Naiads start their dance, and Neptune disappears in the waves of the Nemunas. In writing on the themes of the history of Lithuania, Oderborn relied on Maciej Stryjkowski’s Kronika. In other episodes he uses poetic means of expression from Virgil’s Aeneis, Ovid’s Metamorphoses, Claudian’s Panegyricus de IV consulatu Honorii Augusti, the poem Urania by the Italian humanist Giovanni Gioviano Pontano, the elegy Ad Lunam by the German humanist Peter Lotz (Petrus Lotichius Secundus), and from other Classical, medieval, and Renaissance authors, which is reflected in the language of Hymnus. This poem is an important contribution to the legacy of literary works written by Lithuanian or non-Lithuanian residents of the Grand Duchy of Lithuania in the second half of the sixteenth century.
Keywords: Latin literature of Lithuania; poem; Paul Oderborn; Hymnus de antiqua et illustri Heleboviciorum gente; Jonas Jonaitis Glebavičius; Jan Janowicz Hlebowicz; Grand Duchy of Lithuania